A feasibility and acceptability study of an adaptation of the Mindful Self-Compassion program for adult cancer patients. Issue 2 (April 2020) - Brooker, Joanne; Julian, John; Millar, Jeremy; Prince, H. Miles; Kenealy, Melita; Herbert, Kirsten; Graham, Annette; Smith, Robin; Kissane, David; Taylor, Karen; Frydenberg, Mark; Porter, Ian; et al.
Abstract: Objectives: Psychosocial interventions that mitigate psychosocial distress in cancer patients are important. The primary aim of this study was to examine the feasibility and acceptability of an adaptation of the Mindful Self-Compassion (MSC) program among adult cancer patients. A secondary aim was to examine pre–post-program changes in psychosocial wellbeing. Method: The research design was a feasibility and acceptability study, with an examination of pre- to post-intervention changes in psychosocial measures. A study information pack was posted to 173 adult cancer patients 6 months–5 years post-diagnosis, with an invitation to attend an eight-week group-based adaptation of the MSC program. Results: Thirty-two (19%) consented to the program, with 30 commencing. Twenty-seven completed the program (mean age: 62.93 years, SD 14.04; 17 [63%] female), attending a mean 6.93 (SD 1.11) group sessions. There were no significant differences in medico-demographic factors between program-completers and those who did not consent. However, there was a trend toward shorter time since diagnosis in the program-completers group. Program-completers rated the program highly regarding content, relevance to the concerns of cancer patients, and the likelihood of recommending the program to other cancer patients. Sixty-three percent perceived that their mental wellbeing had improved from pre- to post-program; none perceived a deterioration in mental wellbeing. Small-to-medium effects were observed for depressive symptoms, fear of cancer recurrence, stress, loneliness, body image satisfaction, mindfulness, and self-compassion. Significance of results: The MSC program appears feasible and acceptable to adults diagnosed with non-advanced cancer. The preliminary estimates of effect sizes in this sample suggest that participation in the program was associated with improvements in psychosocial wellbeing. Collectively, these findings suggest that there may be value in conducting an adequately powered randomized controlled trial to determine the efficacy of the MSC program in enhancing the psychosocial wellbeing of cancer patients.